Geomorphology of four wave-dominated microtidal Mediterranean beach systems with Posidonia oceanica meadow: a case study of the Northern Sardinia coast. Issue 2 (30th November 2017) - De Muro, Sandro; Porta, Marco; Passarella, Marinella; Ibba, Angelo
ABSTRACT: The results of this geomorphological study, which focuses on four Mediterranean embayed microtidal wave-dominated beach systems and the related inner shelf, are reported on a detailed geomorphological map (1:12, 000 scale). The study area is located between Punta di Li Francesi and Lu Poltiddolu in NW Sardinia, W of the Strait of Bonifacio. The Main Map presents geomorphological, sedimentological, hydrodynamical and ecological (underwater vegetation) features indicated in nine sections of the map legend. Integrative maps (1:40, 000 scale) of side-scan sonar surveys, sedimentary facies, survey routes and sampling point locations are also represented on the Main Map . This work summarizes 25 years of historical geomorphological datasets and can be considered as a reference for future comparisons of the study area as indicated by current European legislation. In addition to the scientific value of this study, the proposed map can be an important tool for coastal, beach and inner shelf management.